Mastitis Pathogens with High Virulence in a Mouse Model Produce a Distinct Cytokine Profile In Vivo - Johnzon, Carl-Fredrik; Artursson, Karin; Söderlund, Robert; Guss, Bengt; Rönnberg, Elin; Pejler, Gunnar (Frontiers in Immunology, 2016)
Mastitis is a serious medical condition of dairy cattle. Here we evaluated whether the degree of virulence of mastitis pathogens in a mouse model can be linked the inflammatory response that they provoke. Clinical isolates of Staphylococcus aureus (S. aureus) (strain 556 and 392) and E. coli (676 and 127), and laboratory control strains (8325-4 (S. aureus) and MG1655 (E. coli)), were injected i.p. into mice, followed by the assessment of clinical scores and inflammatory parameters. As judged by clinical scoring, E. coli 127 exhibited the largest degree of virulence among the strains. All bacterial strains induced neutrophil recruitment. However, whereas E. coli 127 induced high peritoneal levels of CXCL1, G-CSF and CCL2, strikingly lower levels of these were induced by the less virulent bacterial strains. High concentrations of these compounds were also seen in blood samples taken from animals infected with E. coli 127, suggesting systemic inflammation. Moreover, the levels of CXCL1 and G-CSF, both in the peritoneal fluid and in plasma, correlated with clinical score. Together, these findings suggest that highly virulent clinical mastitis isolates produce a distinct cytokine profile that shows a close correlation with the severity of the bacterial infection.